A SEMI-EMPIRICAL MODEL FOR PREDICTING FLEXURAL STRENGTH OF CNT-REINFORCED CFRP BASED ON TENSILE STRENGTH AND INTERFACIAL CONTRIBUTIONS - To, AnhDuc; Phan, NgocMinh; Bui, HungThang (Vietnam Journal of Science and Technology, 2025)
A semi-empirical model is proposed to predict the flexural strength of CNT-reinforced CFRP composites using tensile strength and CNT concentration as primary inputs. The model incorporates three physically meaningful terms, proportional to , to capture matrix toughening, direct CNT reinforcement, and interfacial efficiency. Model parameters were determined via least-squares regression using experimental data from composites with CNT concentrations up to 0.4 wt%. Validation against independent data (0.5–0.8 wt%) showed strong agreement, with errors consistently below 4%. In addition, the model reflects key trends observed in practice: an increase in tensile strength of approximately 20–25% and in flexural strength of about 30–35% at 0.8 wt% CNTs, relative to the baseline. This formulation offers a balanced compromise between physical realism and predictive simplicity, making it useful for materials selection and mechanical design. Future work will extend the model beyond the saturation point to account for CNT agglomeration, nonlinear interfacial behavior, and morphological effects that emerge at higher loadings